2018
DOI: 10.1111/iwj.13019
|View full text |Cite
|
Sign up to set email alerts
|

Non‐uraemic calciphylaxis successfully treated with pamidronate infusion

Abstract: Calciphylaxis is a rare and potentially fatal disease that affects the subcutaneous layer of the skin. It is a calcific vasculopathy induced by a systemic process that causes occlusion of small blood vessels. The mortality rate for individuals diagnosed with calciphylaxis is estimated between 52% and 81% with sepsis being the leading cause of death. Uraemic calciphylaxis and its known effective treatments are well documented in the literature. Unfortunately, there is no known effective treatment for non‐uraemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…Table 3 summarises the existing published case reports of NUC treated with the IV medications pamidronate, zoledronate, and sodium thiosulfate (STS), as well as intralesional STS. Two studies using IV pamidronate reported complete closure after 6 months of treatment 26,28 . One study using IV pamidronate did not report the outcome of complete closure 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 summarises the existing published case reports of NUC treated with the IV medications pamidronate, zoledronate, and sodium thiosulfate (STS), as well as intralesional STS. Two studies using IV pamidronate reported complete closure after 6 months of treatment 26,28 . One study using IV pamidronate did not report the outcome of complete closure 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Two studies using IV pamidronate reported complete closure after 6 months of treatment. 26,28 One study using IV pamidronate did not report the outcome of complete closure. 28 The report of zoledronate treatment did not report the outcome of complete closure.…”
Section: Discussionmentioning
confidence: 99%
“…The management of CUA remains problematic as clinicians have largely relied on case series and small uncontrolled studies for guidance. Several agents such as sodium thiosulphate, calcimimetics [ 5 ], bisphosphonates [ 6 ] and vitamin K have been identified as showing promise in small studies, although real benefit of these agents in isolation is still under debate [ 7 9 ]. Country-based registries and studies have been a major resource in providing data on the natural history and outcomes of CUA [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…73 The effective use of bisphosphonates has been reported in case series of patients with uremic as well as with non-uremic calciphylaxis. [74][75][76] However, long-term use of bisphosphonates in dialysis patients is usually avoided because of their strong influence on bone metabolism, so any treatment with bisphosphonates should be discussed in an interdisciplinary setting. Another interesting compound for the treatment of calciphylaxis is sodium thiosulfate.…”
Section: Treatmentmentioning
confidence: 99%